Fever in Childhood Infectious Mononucleosis - Skenderi, Elda; Kuli-Lito, Gjeorgjina; Shkembi, Alberta; Shahini, Nilsa; Toci, Griselda; Pema, Ada (International Journal For Research In Health Sciences And Nursing, 2021)
Fever is one of the oldest clinical indicators of disease and one of the most common reasons for medical attention worldwide especially in children. The febrile response is a significant contributor to the pathogenesis, clinical presentation and outcome of many diseases. Infectious Mononucleosis, which is the most common clinical manifestation caused by EBV infection, usually begins insidiously, with vague malaise, followed by fever, sore throat, swollen posterior cervical lymph nodes and fatigue. Of the 107 children with Infectious Mononucleosis enrolled in the study 97% had fever. Fever was the first symptom in 84% of those. 29% of children experienced high levels of fever >40°C. There was an association statistically significant between the duration of fever: levels of lymphocytes, levels of alanine aminotransferase, and levels of anxiety. As a conclusion it can be stated that fever is the most common symptom in children with Infectious Mononucleosis. Compared to older children, infants and young children experience higher and more prolonged fevers, more rapid temperature increases, and greater temperature fluctuations. The duration of fever in Infectious Mononucleosis is much longer than in most other viral infections of childhood. The potent innate and adaptive immune response, which occurs during primary EBV infection controls infection and is responsible for the most symptoms and signs of the disease including fever.